Case report: A safeguard in the sea of variants of uncertain significance: a case study on child with high risk neuroblastoma and acute myeloid leukemia - Fabozzi, Francesco; Carrozzo, Rosalba; Lodi, Mariachiara; Di Giannatale, Angela; Cipri, Selene; Rosignoli, Chiara; Giovannoni, Isabella; Stracuzzi, Alessandra; Rizza, Teresa; Montante, Claudio; Agolini, Emanuele; Di Nottia, Michela; et al. (Frontiers in Oncology, 2024)
The increased availability of genetic technologies has significantly improved the detection of novel germline variants conferring a predisposition to tumor development in patients with malignant disease. The identification of variants of uncertain significance (VUS) represents a challenge for the clinician, leading to difficulties in decision-making regarding medical management, the surveillance program, and genetic counseling. Moreover, it can generate confusion and anxiety for patients and their family PAGE \* Arabic \* MERGEFORMAT This is a provisional file, not the final typeset article members. Herein, we report a 5-year-old girl carrying a VUS in the Succinate Dehydrogenase Complex Subunit C (SHDC) gene who had been previously treated for high-risk neuroblastoma and subsequently followed by the development of secondary acute myeloid leukemia. In this context, we describe how functional studies can provide additional insight on gene function determining whether the variant interferes with normal protein function or stability.